2016
DOI: 10.1038/srep22671
|View full text |Cite
|
Sign up to set email alerts
|

The Silk-protein Sericin Induces Rapid Melanization of Cultured Primary Human Retinal Pigment Epithelial Cells by Activating the NF-κB Pathway

Abstract: Restoration of the retinal pigment epithelial (RPE) cells to prevent further loss of vision in patients with age-related macular degeneration represents a promising novel treatment modality. Development of RPE transplants, however, requires up to 3 months of cell differentiation. We explored whether the silk protein sericin can induce maturation of primary human retinal pigment epithelial (hRPE) cells. Microarray analysis demonstrated that sericin up-regulated RPE-associated transcripts (RPE65 and CRALBP). Ups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 67 publications
2
23
0
Order By: Relevance
“…Furthermore, IPA analysis of the proteomic dataset predicted that the NF-κB pathway, important in pro-inflammatory signaling, was upregulated in RPE cultured in DMEM with 1% sericin. This is in agreement with a previous transcription analysis report by our group in which we demonstrated that sericin conduces pigmentation of RPE by activating the NF-κB pathway [ 8 ]. Despite the higher levels of inflammation-associated proteins, and the predicted activation of the NF-κB pathway in sericin-supplemented RPE cultures, significantly higher cell viability was observed in these cultures compared to cells cultured without sericin.…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…Furthermore, IPA analysis of the proteomic dataset predicted that the NF-κB pathway, important in pro-inflammatory signaling, was upregulated in RPE cultured in DMEM with 1% sericin. This is in agreement with a previous transcription analysis report by our group in which we demonstrated that sericin conduces pigmentation of RPE by activating the NF-κB pathway [ 8 ]. Despite the higher levels of inflammation-associated proteins, and the predicted activation of the NF-κB pathway in sericin-supplemented RPE cultures, significantly higher cell viability was observed in these cultures compared to cells cultured without sericin.…”
Section: Discussionsupporting
confidence: 94%
“…These findings are supported by reports proposing sericin-associated superoxide dismutase activity [ 25 , 26 ]. Moreover, through Affymetrix microarray analysis, we recently reported that sericin upregulates superoxide dismutase genes in RPE cultured with sericin [ 8 ]. Superoxide dismutase is an enzyme that catalyzes the dismutation of superoxide into oxygen, water and hydrogen peroxide.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations